Biocasting of an elastin-like recombinamer and collagen bi-layered model of the tunica adventitia and external elastic lamina of the vascular wall. (23rd April 2021) - González-Pérez, Miguel; Camasão, Dimitria Bonizol; Mantovani, Diego; Alonso, Matilde; Rodríguez-Cabello, José Carlos
Abstract : Biocasting of a bi-layered model of the external elastic lamina and the tunica adventitia of the vascular wall from a fibroblast cellularized collagen and a click crosslinkable, cell-adhesive and protease-sensitive elastin-like recombinamer hydrogel. Abstract : The development of techniques for fabricating vascular wall models will foster the development of preventive and therapeutic therapies for treating cardiovascular diseases. However, the physical and biological complexity of vascular tissue represents a major challenge, especially for the design and the production of off-the-shelf biomimetic vascular replicas. Herein, we report the development of a biocasting technique that can be used to replicate the tunica adventitia and the external elastic lamina of the vascular wall. Type I collagen embedded with neonatal human dermal fibroblast (HDFn) and an elastic click cross-linkable, cell-adhesive and protease-sensitive elastin-like recombinamer (ELR) hydrogel were investigated as readily accessible and tunable layers to the envisaged model. Mechanical characterization confirmed that the viscous and elastic attributes predominated in the collagen and ELR layers, respectively. In vitro maturation confirmed that the collagen and ELR provided a favorable environment for the HDFn viability, while histology revealed the wavy and homogenous morphology of the ELR and collagen layer respectively, the cell polarization towards the cell-attachment sites encoded on the ELR, and the enhanced expression of glycosaminoglycan-rich extracellular matrix and differentiation of the embedded HDFn into myofibroblasts. As a complementary assay, 30% by weight of the collagen layer was substituted with the ELR. This model proved the possibility to tune the composition and confirm the versatile character of the technology developed, while revealing no significant differences with respect to the original construct. On-demand modification of the model dimensions, number and composition of the layers, as well as the type and density of the seeded cells, can be further envisioned, thus suggesting that this bi-layered model may be a promising platform for the fabrication of biomimetic vascular wall models.